Urban and periurban agriculture in the cuban cities of Camaguey and Cienfuegos - Moreira Santos, Erika Vanessa; Medeiros Hespanhol, Rosangela Aparecida de [UNESP]; Moreno Lorenzo, Xiomara A. (Revues Org, 2020)
The main objective of this text was to perform a descriptive analysis of urban and periurban agriculture in two cuban medium cities - Camaguey and Cienfuegos, aiming to understand the importance of this economic activity for the structuring of these cities. To achieve this work, the following methodological procedures were necessary: survey of bibliographic materials and data from secondary sources collected in Cuban state institutions - Center for Demographic Studies (CEDEM), Center for the Study of the Cuban Economy (CEEC), National Library of Havana, Provincial Directorate of Physical Planning of the cities of Camaguey and Cienfuegos (DPPF), and field research for the collection of materials and obtaining information on site, in organophonics of Cienfuegos and Camaguey. Cuban urban agriculture policy is a reference for the whole world, based on agroecological principles and promoted within a state project aimed at food sovereignty. In the specific case of the studied municipalities, the most common modality was the cultivation in organophonics, whose sale of cultivated products is directly to the consumer. In addition, the development of this activity is incorporated into the ordering plans of these cities.
Keywords: urban agriculture; periurban agriculture; Cuba; commercialization